Pulmonary fibrosis in sarcoidosis - Asif, Huda; Ribeiro Neto , Manuel; Culver, Daniel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Sarcoidosis may progress to pulmonary fibrosis in 5% of patients with significantly increased mortality. Histopathology shows fibrosis in a lymphangitic pattern surrounding the granulomas. Th1 to Th2 shift in environment along with angiogenesis is implicated in exuberant fibrosis. Clinical features include dyspnea, cough, and frequently with pulmonary function tests showing a mixed ventilatory defect with severely decreased diffusion capacity of carbon monoxide.  Serologic markers including soluble interleukin 2 receptor, chitotriosidase and kern von den lunges 6, and chemokine ligand 18 are elevated and implicated in progression of disease. CT imaging shows fibrosis along bronchovascular bundles with reticulations, traction bronchiectasis and honeycombing predominantly in the upper and central distribution. Complications include sarcoidosis-associated pulmonary hypertension (SAPH) and chronic pulmonary aspergillosis. Treatment involves glucocorticoids and steroid-sparing agents in the presence of active granulomas. Anti-fibrotic agents such as pirfenidone and nintedanib have been shown to slow down pulmonary function decline in randomized clinical trials involving sarcoidosis-associated pulmonary fibrosis. Transplant workup is indicated in New York Heart Association class III or IV with similar success rates as in other lung transplant patients.